A Deep Learning–Based Islamic Education Learning Model for Developing Students’ Higher Order Thinking Skills - Rizki, Moch; Asrori, Asrori; Hidayat , Moch Charis (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2026)
This study examines the construction, implementation, and contribution of a deep learning–based Islamic education learning model to the development of Higher Order Thinking Skills (HOTS) among primary school students. It employs an interpretive qualitative approach with an intrinsic case study design and was conducted at SD Muhammadiyah 21 Surabaya. Data were collected through classroom observations, in-depth interviews, and document analysis, and were thematically analyzed using reflective coding techniques. The findings indicate that the deep learning–based Islamic education model emphasizes deep conceptual understanding, reflective dialogue, contextual learning, and the internalization of Islamic values. The implementation of this model shifts Islamic education instruction from a normative, memorization-oriented approach to meaningful, dialogical learning. Empirical evidence further demonstrates that the model is effective at fostering students’ analytical, evaluative, and reflective thinking abilities while strengthening moral awareness and character formation.